A Study to Evaluate the Knowledge of Menstrual Cups Among Engineering Students at Selected Colleges in Kuppam, Andhra Pradesh - M.N. Pavithra; V. Divya Sri; M. Abhirami; Melvin David; K. Daniel Arun Kumar; Karthika P.; Kumari; Jisna Jose; K.S. Aswini (International Journal of Women's Health Nursing And Practices, 2024)
Background and Aims:Menstrual cups are an eco-friendly and cost-effective alternative to sanitary pads, yet they have not gained widespread popularity among Indian women. This study aims to evaluate the knowledge of menstrual cups among engineering students at selected colleges in Kuppam, Andhra Pradesh, to better understand awareness and acceptance of this alternative menstrual product. Materials and Methods: A cross-sectional descriptive research design was employed. A total of 143 engineering students were selected using a non-probability convenience sampling method. Data were collected through a structured questionnaire assessing the students' knowledge of menstrual cups, categorized into three levels: inadequate, moderate, and adequate. Results: The findings revealed that the majority of students, 103 (72%), had moderate knowledge about menstrual cups. A smaller group, 28 (19.6%), had inadequate knowledge, while 12 (8.4%) students demonstrated adequate knowledge. Conclusion: The results suggest that engineering students possess a moderate level of knowledge regarding menstrual cups, indicating some awareness of this alternative menstrual hygiene product. However, despite the numerous advantages of menstrual cups—such as being eco-friendly, cost-effective, and helping prevent reproductive tract infections—their usage appears to be limited. These findings underscore the need for targeted educational programs to enhance knowledge and promote the adoption of menstrual cups among Indian students, thereby increasing their prevalence and encouraging healthier menstrual practices,
Keywords: Knowledge; Menstrual cup; engineering Students